(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
The importance of innovation as an instrument in service delivery and building greater trust towards public service and the government, is undeniable. Prior studies in the literature on the public sector domain revealed that innovation in the public sector may result in a positive impact on the government, the public, organizations as well as the nation as a whole. Although there is point of similarity and convergence between public and private sector innovation, it is arguable that complexity in the public sector suggests that the general assumption that practices from the private sector are the best references for improving public sector innovation. A review of the body of literature on various concepts of innovation from both public and private sector perspectives has found significant demarcation between innovations in both sectors in terms of objectives, governance model for innovation, dimensions and diffusion of innovation. The findings suggest a need for a dedicated concept in understanding public sector innovation, rather than implementing a ‘one-size-fits-all’ approach of innovation by adopting from the private sector. The correct conceptualization of public sector innovation will lead to the formulation of the right policy to support innovation, appropriate business models, implementation of crucial initiatives, innovation process improvements, and measurements to gauge the performance of public sector innovation.